CHARACTERISTICS OF MEASLES SPREAD AMONG CHILDREN UNDER ONE YEAR OF AGE - Masharipova , Shakhista (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Measles is a highly contagious viral disease that is particularly dangerous in children under one year of age due to its severe course and risk of complications. This study analyzed the characteristics of measles spread, risk factors, and clinical course among children under one year of age during 2024–2025. Medical records of 42 patients were retrospectively analyzed. The results showed that most cases occurred in unvaccinated children and were associated with household contact. Clinically, moderately severe forms predominated, while complications were observed in some cases. The findings confirm the importance of early prevention and vaccination.